Population genetic structure of the Atlantic Forest endemic Conopophaga lineata (Passeriformes: Conopophagidae) reveals a contact zone in the Atlantic Forest - Dantas, Gisele Pires Mendonça (2014)
The Rufous Gnateater, Conopophaga lineata, is a small insectivorous understory bird which is endemic to and widely distributed in the tropical and subtropical Atlantic forest of South America. Its distribution makes it ideally suited for testing two major hypotheses for the origin of biodiversity, namely, the riverine barrier and the forest refuge hypotheses. In this study, we sequenced mitochondrial (control region) and nuclear markers (intron 5 of the β-fibrinogen gene) for individuals distributed in the southern Atlantic forest and obtained a strong genetic structure with one clear discontinuity in northern Brazilian state of São Paulo. We consistently detected signals of demographic expansion for both markers, with estimates indicating that expansion started in the Late Pleistocene (250,000 years ago), suggesting that the forest refuge hypothesis potentially explains Rufous Gnateater’s diversification. We also found evidence of gene flow between populations from each side of this discontinuity, with a possible secondary contact zone occurring in the states of Minas Gerais, São Paulo, and Rio de Janeiro.